Rhipidia crane flies (Diptera: Limoniidae) from Korea - Podenas, Sigitas; Byun, Hye-Woo; Kim, Sam-Kyu (Zootaxa, 2016)
Korean species of the crane fly genus Rhipidia Meigen, 1818 (Diptera: Limoniidae), are taxonomically revised. Rhipidia (Rhipidia) serena, new species, is described and figured. Rhipidia (R.) longa Zhang, Li, Yang, 2014, R. (R.) maculata Meigen, 1818 and R. (R.) sejuga Zhang, Li, Yang, 2014 are recorded for the first time in Korea. Previously known species, Rhipidia (R.) septentrionis Alexander, 1913 is redescribed and illustrated. Identification key for all Korean Rhipidia species is given. Most antennae, wings, male and female terminalia of all species are illustrated for the first time.